(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The term "political mobilization" refers to the steps used to get people to take a stand on a particular political issue. Each country’s youth, including those who were unhappy with autocratic regimes and wanted more democratic leadership, formed a separate organization. Members of unions, who were also a distinct category, were under continual attack in these nations. The younger generation and union members who are fighting for political representation and identity recognition are both seen as part of the movement to bring about change within the context of this conversation. Major consequences for political science are associated with political identity, which stands for people’s core values, objectives, and ambitions. Furthermore, while assessing the factors that lead to conflicts, it is crucial to consider this element. With a politically homogenous population, it could be simpler to pass laws and enact policies that reflect the values held by the people living in that state. They were able to use their neighborhood connections to their political advantage. They also did a lot of door-to-door canvassing and recruited neighbors to join their political parties. Their enthusiasm for democratic philosophy and political politics was evident. When it came to protecting their communities’ interests, they trusted their political parties. Minority political figures are rising to prominence in the Hyderabad Karnataka Region. The OBCs in the Hyderabad, Karnataka region were politically mobilized due to the influence of previous community leaders.